Recovery of Yttrium Oxide from Titanium-Aluminium based wastes - Srećko Stopić; Sebastian Kallabis; Bernd Friedrich (Journal of Engineering & Processing Management, 2018)
Yttrium belongs to the rare earth elements and critical metals.Yttrium oxide is mostly used in fluoroscent lamps, production ofelectrodes, in electronic filters, lasers, superconductors and asadditives in various titanium-aluminium materials to improve theirproperties. Recovery of yttrium oxide from secondary sourcessuch as red mud, coatings from ceramic industry and phosphors isextremely important. The main aim of this study is to examine theselective recovery of yttrium oxide from Al-Ti based secondarymaterials using one combined method based mostly on leachingfor selective recovery of yttrium containing: crashing and grindingof materials, sieving, leaching of chosen fine fraction withhydrochloric acid, precipitation with oxalic acid in order to producea pure yttrium oxalate, filtration and a final thermal decompositionof yttrium oxalate. The present study summarized mostly theinfluence of different reaction parameters such as leachingtemperature, time and concentration of hydrochloric acid onyttrium dissolution from Al-Ti based secondary materials. Anincrease of dissolution time and temperature increases yttriumdissolution. An increase of pressure from an atmospheric pressureto 0.5 MPa at 150 ℃ leads to the maximum dissolution of yttrium(about 98.6 %). The final produced yttrium oxide after thermaldecomposition of yttrium oxalate was analyzed using SEM andEDS-analysis.
Keywords: yttrium oxide; hydrometallurgy; leaching; recycling